Impact of Bottom Trawling on Sediment Texture and Organic Matter Along Inshore Waters of Kerala (South India) - Thomas, Joice V.; B., Madhusoodana Kurup (Fishery Technology, 2025)
Sediment texture and organic matter were analysed before and after trawling in samples collected from 0-50 m depth zone during December 2000-November 2001, along Kerala coast (Long. 75Â° 56/00 to 76o10’ and Lat. 9058’ to 10010’). Up to 40 m depth the composition of sand, silt and clay were 0.19 - 15.8%, 35.33 -60.53% and 29.9 - 53.12% respectively. Beyond ’ this, sand was dominant (sand 32.6 - 96.15, silt 1.8 - 33.8, clay 2.45- 26.48%). In samples collected before trawling, sand, silt and clay ranged from 4.76 - 87, 45.85-55.71 and 43.18 - 47.38% respectively. In the samples collected after trawling the corresponding values for sand, silt and clay were 21.25 - 35.7, 51.28 -63.92 and 13.03 - 21.6% respectively. Organic carbon in 0-30 m depth zone ranged from 0.229 - 7.68% and it showed highest variations in July especially at depths 0-10 m and 10-20 m with respective values of 4.45 and 4.75% before trawling; while in the after trawling samples it was reduced to 2.21 % and 1.90% respectively. The sand and silt fractions showed a significant increase whereas a drastic reduction in clay fraction was observed especially in 0- 40 m depth zone due to bottom trawling.